Método multirresíduo de agrotóxicos em polpa de açaí empregando método QuEChERS modificado e UHPLC-MS/MS - Rafael Bel Prestes da Silva; Luana Floriano; Cleusa Fátima Zanchin; Franciele Fátima Machado; Júlia Antunes de Oliveira; Osmar Damian Prestes; Renato Zanella (Química Nova)
The northern region of Brazil, particularly the states of Pará and Amazonas, concentrates the majority of açaí national production. Considering the possible use of pesticides in this species, this study aimed to develop a comprehensive method for the multiresidue determination of pesticides in açaí pulp, using a modified QuEChERS (quick, easy, cheap, effective, rugged, and safe) method with analysis by ultra-high performance liquid chromatography with tandem mass spectrometry (UHPLC-MS/MS). Various parameters of extraction were investigated, and the method was successfully validated. Analysis by UHPLC-MS/MS provided high selectivity and sensitivity. The main modification to the original QuEChERS method was the use of the C18 adsorbent associated with primary secondary amine (PSA) in the clean-up step by dispersive solid phase extraction (d-SPE). The method was validated for 83 compounds, showing adequate accuracy (70 to 120%) and precision (RSD ≤ 20%). The method limits of quantification, established by recovery tests, ranged from 5 to 25 µg kg-1. The method limits of detection were from 1.5 to 7.5 µg kg-1. The method was applied to commercial samples of açaí pulp, and no pesticide residues were detected. The proposed method proved to be fast, efficient and suitable for multiresidue determination of pesticides in açaí pulp in routine analysis.